Development of unmanned surface vehicle with real-time water quality monitoring system - Mohamed Kassim, Anuar; Jamri, Mohd Saifuzam; Mohd Aras, Mohd Shahrieel; Ab Wahab, Norfariza; Jaya, A.K.R.A.; Yasuno, Takashi (2023)
Conventionally, the water sample need to be sent to laboratory for lab analysis and take about 2-3 months. Therefore, the development and analysis of on-the-go water monitoring system using unmanned surface vehicle (USV) is proposed. The developed USV with the water monitoring system can measure and analyze the water pollution on the-go to and real time to determine the pollution level. The ISE sensor such as temperature, pH, electrical conductivity (EC), oxidation reduction potential (ORP), dissolved oxygen (DO) and turbidity with the GPS device is used on the. The USV also developed with auto navigation through all the targeted area by using GPS coordinate and path planning algorithm programmed in the USV controller. In this project, we use the IoT application to store data in the cloud and to dispense the information. The correlation of the ISE sensor and the lab analysis will be done. This system will also give out status of the water quality and immediate warning if the water is in the bad quality for further action to be taken by the management of the reservoir. Last but not least, the contribution of this research is that the use of USV helps to improve sensing and monitoring of water quality in remote area.